The Application Of Mind Mapping Technique To Improve Students Speaking Skills - Roriwo, Wiwin Sahertian; Mogea, Tni; Wongkar, Yapi (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2025)
Abstract : The skill in communicating is speaking, speaking is one of the basic skills that a person be able to communicate with others, but there are several problems, namely not everyone can speak well, especially speaking in public or only with people. The aim of this research is to improve skills, namely speaking to students. This research is also classified as classroom action research which is carried out in the form of two cycles. And the subjects involved in this research were 20 students’ of Smp Negeri Satap Buo class VIII. In this research, data collection was carried out using observation, test and interviews. The instruments given by the researchers were speaking ability test and providing observation sheets. The results of this research showed that students gained significant improvement after the researchers introduced several conversations into English languange learning for students’. The students’ pre-test results obtained the lowest score of 55,75 but after the researchers provided treatment through conversation and several examples of making mind mapping to students’. The students’ post-test results obtained the highest score of 68,5. This means that the Application of Mind Mapping method was successful in teaching and learning English for students’.